The relationship between mental habits and problem-solving styles among graduate students at Sana'a University - Nasser Ali Albaddai (Social Empowerment Journal, 2025)
This study aimed to explore the level of mindsets and problem-solving skills among graduate students at Sana'a University, as well as to analyze the relationship between these two variables. A descriptive approach was used to achieve the study's objectives, with a stratified random sample of 80 students from the master's and doctoral levels across various colleges and research centers. The "Mindsets" scale (Abu Latifa, 2019) and the "Problem-Solving" scale (Abdulazim, 2013) were applied to the study sample, and the validity and psychometric efficiency of the tools were verified in the Yemeni context. The results showed that graduate students at Sana'a University possess high levels of mindsets and problem-solving skills, with a strong correlation between the dimensions of the two scales. Additionally, no significant differences were found for either scale based on the variables of gender and academic level.